Supply Chain Risk Mitigation Analysis on Coffee Comodities Using the Integration of FMEA and HOR Methods - Wulansari, Ni Luh Made Pretty; Pulansari, Farida (Rekayasa, 2024)
Coffee has been a global commodity since its discovery, so it's not surprising that there are various coffee cultivation variations in different regions. Economically, coffee plays a significant role in coffee-producing countries, including Indonesia, where it is cultivated and produced. The company is one of the companies engaged in the manufacturing of powdered coffee production. In its efforts to meet market targets, the company faces challenges. Therefore, a supply chain analysis is conducted on the coffee production process to identify occurring risks. The resolution of issues in this research utilizes the integration of FMEA and HOR methods. The application of these integrated methods about supply chain risk mitigation analysis has also been widely developed. Based on the risk identification results in HOR stage I, there are 17 risk events caused by 25 risk causes. Out of 25 risk causes, 11 dominant risk causes are obtained based on ARP calculations. Then, in HOR stage II, 17 mitigation steps are designed to prevent or minimize the 11 dominant risks obtained from the HOR phase I calculations. After calculating the total effectiveness and degree of difficulty, the results of the mitigation effectiveness ranking based on the difficulty ratio (ETDk) with the highest value carried out routine preventive maintenance on milling equipment to prevent damage and process instability (PA 7) of 16143.21, and the last rank prepared a backup of coffee machines or critical components to reduce production downtime (PA 16) of 1406.16.